Human Leukocyte Antigen Fine-Mapping and Correlation Analysis of Han and Minority Leprosy Patients in Southern China - Li, Zhuo; Wang, Yirui; Fan, Wencheng; Zhang, Chang; Liu, Hao; Zhang, Ruixue; Cao, Lu; Zhen, Qi; Chen, Weiwei; Yu, Yafen; Li, Bao; Mao, Yiwen; et al. (Frontiers in Genetics, 2022)
BACKGROUND: Leprosy is very prevalent in many populations around the world, which is well known that both alleles for human leukocyte antigen (HLA) as well as single nucleotide polymorphisms (SNPs) in the HLA region are common in leprosy patients. Previous studies have identified leprosy-associated susceptibility genes that explain only part of disease risk and heritability. In view of the complicated characteristics of the major histocompatibility complex (MHC) region, this study aimed to explore the development and variation of HLA in leprosy and its possible mechanism. METHODS: Previous genome-wide association data were extracted from Han and minority populations in southern China for HLA fine-mapping studies. Insertion and deletion (INDEL), SNP, and copy number variation (CNV) imputation were determined by using the Thousand People Database (1KGP Phase 3 Dataset) as a reference panel. The HAN-MHC database was used to input the HLA classical alleles and amino acids in the MHC region, and further step-regression analysis was performed to analyze independent variation signals associated with leprosy. RESULTS: The most significant locus rs75324027（the same locus as rs602875 in the HLA-DR region） [P = 7.49E-09, OR= 0.62, 95%,CI: 0.52–0.73] in the intergene region between HLA-DQA1 and HLA-DRB1 was related with leprosy in M-S(Han leprosy patients in south China)disease. In M-SM (Leprosy patients of ethnic minorities in south China)disease, one of the most significant loci of the HLA-DQB1 gene was 6-32626438-A-T (P = 4.49E-08, OR = 0.36, 95%,CI: 0.25–0.52). Therefore, rs75324027 is a locus in M-S disease, and 6-32626438-a-T may be a new locus in M-SM disease. The interaction between 6-32626438-A-T and RS75324027 was analyzed, and A significant interaction relationship was found. In the optimal model, the accuracy of prediction was 0.5974, cross-validation Consistency:10, P = 0.0107. CONCLUSIONS: In conclusion, this study is the first to assess the association between HLA and leprosy susceptibility in Han and other minority populations in southern China using the Thousand Population database and the Han MHC database. In addition, our analysis validated the previously reported locus rs602875 in the HLA-DR region and for the first time identified an unreported independent locus in leprosy among ethnic minorities in southern China.